Is Caffeine Recommended Before Exercise? A Systematic Review To Investigate Its Impact On Cardiac Autonomic Control Via Heart Rate And Its Variability. (17th August 2020) - Benjamim, Cicero Jonas R.; Kliszczewicz, Brian; Garner, David M.; Cavalcante, Taisy Cinthia Ferro; da Silva, Amanda Alves Marcelino; Santana, Milana Drumond Ramos; Valenti, Vitor E.
Abstract: Evaluating different doses of caffeine (CAF) on heart rate (HR) variability (HRV) during and following exercise in order to assess its impact on autonomic control. We intended to evaluate the influence of CAF as a supplement before exercise on HRV through a systematic review. Manuscripts were selected based on electronic searches of MEDLINE, EMBASE and CINAHL databases from 2010 to 2019 and followed the protocol Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Blind randomized designs and controlled trials that reported the influence of CAF on HRV during exercise and during recovery from exercise, with strength of evidence assessed using the GRADE system; the search for the studies was organized using the PICOS strategy. A total of 1797 articles were recognized, following the screening and eligibility stages, 9 studies continued to the final sample. Six studies reported that the combination of CAF supplementation with physical exercise exhibited higher HR when compared to the placebo group during post-exercise recovery; additionally, prolonged activation of sympathetic cardiac control and delayed parasympathetic reactivation following exercise was observed. However, three studies demonstrated no CAF influence when using similar doses. This review observed equivocal results in HR and HRV recovery following exercise with the presence of CAF consumption. These findings cannot confirm the cardiac autonomic changes observed where entirely due to the influence of CAF, and further studies should be performed to better understand this relationship. KEY TEACHING POINTS: CAF increased HR during exercise and throughout the recovery period. CAF prolonged post exercise sympathetic activity. CAF delayed vagal reactivation. Deviations in HRV and HR are dependent on the combination of three main factors: CAF dosage, type of exercise, and cardiorespiratory fitness.